Über das Integrieren eines linearen Systems von Differentialgleichun gen in geschlossener Form - Merkys, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Меркис. Об интегрировании в замкнутой форме некоторых линейных систем дифференциальных уравненийV. Merkys. Kai kurių tiesinių diferencialinių lygčių sistemų integravimas baigti pavidalu